POST-TRAINING ASSESSMENT OF DIARRHOEA MANAGEMENT WITH SALT SUGAR SOLUTION BY COMMUNITY-BASED DISTRIBUTION WORKERS IN AKINYELE LOCAL GOVERNMENT AREA, OYO STATE (1995)
Studies in a number of pilot Community Based Distribution (CBD) programmes have shown that CBD workers can deliver modern contraceptives and safe maternal and child health services (including treatment or management of common childhood diseases such as diarrhoea) in their communities (Weiss, 1985). CBD workers have been active in Akinyele Local Government Area (LGA) and a high number of diarrhoea episodes have been managed by them. Most efforts have been on the general assessment of service delivery and also certain issues such as increasing availability of contraceptives have been addressed by CBD workers. One major problem is lack of specific post-training assessment of CBD workers' skill in preparing and use of some of the innovative training packages especially the use of salt sugar solution (SSS) in the management of children diarrhoea diseases. A descriptive study was carried out in five CBD centres of Akinyele LGA between June 1990 and October 1990. All the CBD workers identified were 91 but after four visits to each home, a sample of 77 was found and was interviewed and observed. Baseline information on CBD workers who had managed diarrhoea cases were obtained from records at CBD office. The ammended final draft of the questionnaire after pretest at Ajia in Afijio Local Government Area was administered to the 77 workers. In addition observation with a checklist was used to assess workers' ability to prepare SSS. The respondents were similar in age, occupation (other than CBD work) religion. Though while all Traditional Birth Attendants (TBAs) were female and aged above 45 years, Village Health Workers (VHWs) included both male and female and some aged less than 45 years. All the workers, irrespective of either VHWs or TBAs recognised diarrhoea as a servere case and could relate the causes and management but only 9.1% (2 TBAs, 5 BHWs) could assert the correct preventive measures. All the categories of workers asserted that they have heard of SSS but 14.3% (6 VHWs, 5 TBAs) of the workers could state the correct measurements of SSS though 72.7% used it in diarrhoea management, however 27.3% workers have never used it. More than one third (36.7%) of the workers stated that SSS stops diarrhoea rather than preventing dehydration which was mentioned by only 16.3%. All the workers (100%) mentioned that the ingredients - salt and sugar are expensive though they will continue to use it in future unless there is a new technological breakthrough. However, the workers (97.4%) do not teach mothers who utilize their services. Results from observation study revealed that all the workers (100%) did not have SSS corner and sugar was readily accessible in 48.1% of the homes. The workers' preparation of SSS revealed inadequacy in the skills. The study has demonstrated that operation research can reveal hidden facts which could have been overlooked if research was on a general scope. Based on findings, the researcher recommends that workers undergo refresher training which will emphasise measurements of SSS ingredients, SSS use and preparation. Workers should also have SSS corner in their homes where they can teach mothers and should be compensated financially or in kind as this will motivate workers to be dedicated. Specifically, future study should focus on the diarrhoea occurrence among under five children in the five CBD centres of Akinyele Local Government.